Analysis of the Effect of Load Changes on the Turning and Incoming Power of the Winding Rotor 3-Phase Induction Motor: Analisis Pengaruh Perubahan Beban Terhadap Putaran dan Daya Masuk Motor Induksi 3 Fasa Rotor Belitan - abdul muis prasetia (Electrician : Jurnal Rekayasa dan Teknologi Elektro, 2024)
The 3-phase induction motor is a commonly used motor type in various industries due to its advantages in cost, size, and durability. Despite its significant benefits, such as high torque and good efficiency, this motor is still susceptible to several factors that can affect its performance, with load changes and overloads being among the primary causes. Overloads can result from system overload, lack of maintenance, or suboptimal environmental conditions. The impact of these overloads can lead to reduced efficiency and torque in the 3-phase induction motor, potentially harming the overall system performance. This study focused on using braking loads as a form of load testing. The method implemented involved automatic measurement and calculation, displaying outputs such as slip, input power, induced torque, output power, and efficiency. Based on the results of this study, variations in the applied load affected the motor's torque values, with torque increasing as the load was periodically increased: at 75% load, the torque was 0.857 Nm; at 100% load, it was 0.947 Nm; and at 125% load, it was 0.936 Nm. The motor slip values at 75%, 100%, and 125% loads were 9.3%, 10.8%, and 12%, respectively. The input power values at 75% load were 530.6 Watts, at 100% load were 587.54 Watts, and at 125% load were 623.57 Watts. The efficiency values at 75% load were 23.23%, at 100% load were 22.77%, and at 125% load were 20.85%. From the data obtained, it could be seen that the input power continuously increased with the load, the motor slip increased, and the best efficiency occurred when the motor operated at a 75% load.